Direct high-purity hydrogen production from ammonia by using a membrane reactor combining V-10mol%Fe hydrogen permeable alloy membrane with Ru/Cs2O/Pr6O11 ammonia decomposition catalyst. (12th February 2022) - Omata, Kaori; Sato, Katsutoshi; Nagaoka, Katsutoshi; Yukawa, Hiroshi; Matsumoto, Yoshihisa; Nambu, Tomonori
Abstract: The hydrogen production capabilities of the membrane reactor combining V-10 mol%Fe hydrogen permeable alloy membrane with Ru/Cs2 O/Pr6 O11 ammonia decomposition catalyst are studied. The ammonia conversion is improved by 1.7 times compared to the Ru/Cs2 O/Pr6 O11 catalyst alone by removing the produced hydrogen through the V-10mol%Fe alloy membrane during the ammonia decomposition. 79% of the hydrogen atoms contained in the ammonia gas are extracted directly as high-purity hydrogen gas. Both the Ru/Cs2 O/Pr6 O11 catalyst and the V-10 mol% Fe alloy membrane are highly durable, and the initial performance of the hydrogen separation rate lasts for more than 3000 h. The produced hydrogen gas conforms to ISO 14687–2:2019 Grade D for fuel cell vehicles because the ammonia and nitrogen concentrations are less than 0.1 ppm and 100 ppm, respectively. Graphical abstract: Image 1 Highlights: Reactor combing V-alloy membrane and Ru catalyst for H2 production from NH3 . High purity H2 conforming to ISO standards for FCV is produced directly from NH3 . NH3 conversion of Ru catalyst increases 1.7 times by combining with V-alloy membrane. 79% of the H contained in the supplied NH3 is directly extracted as high purity H2 . The stable H2 separation flux lasts for more than 3000 h.